Suggestions for the simplification of the procedure in relation to the sale of land in Ireland - Lynch, Stanislaus J. (Statistical and Social Inquiry Society of Ireland, 1885)
I am indebted to the Council of your Society for the privilege of submitting for your consideration this evening, some suggestions for the simplification of the procedure in relation to the sale of land in Ireland, and I feel that I have only to call attention to the condition of the Irish land market during the past four years, to convince you of the urgent necessity for immediate legislation, in order to give vitality to the purchase clauses of the Land Act of 1881.
Read before the Society, 28 April 1885
Keywords: Irish land question; Irish Land Act, 1881; Land sales; Irish land market; Irish agriculture; 314.15